2020
DOI: 10.1136/ijgc-2020-001612
|View full text |Cite
|
Sign up to set email alerts
|

Limited frequency of malignant change in lobular endocervical glandular hyperplasia

Abstract: IntroductionAlthough lobular endocervical glandular hyperplasia is a benign disorder of the uterine cervix, its potential as a precursor of minimal deviation adenocarcinoma has been reported. However, the natural history of the disease and the frequency of malignant change are not fully understood. We evaluated the frequency of malignant change of clinical lobular endocervical glandular hyperplasia and explored useful parameters indicating malignant change.MethodsThe clinical courses of 175 patients with cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 16 publications
(22 reference statements)
0
20
1
Order By: Relevance
“…Especially, AGC‐NOS suggested benign (nonatypical) LEGH, whereas AGC‐FN suggested atypical LEGH or MDA/GAS 44,45 . Collectively, cervical cytology is useful to distinguish benign LEGH and MDA/GAS/atypical LEGH 14,26,42 . (Figure 6a, b).…”
Section: Clinical Managementmentioning
confidence: 98%
“…Especially, AGC‐NOS suggested benign (nonatypical) LEGH, whereas AGC‐FN suggested atypical LEGH or MDA/GAS 44,45 . Collectively, cervical cytology is useful to distinguish benign LEGH and MDA/GAS/atypical LEGH 14,26,42 . (Figure 6a, b).…”
Section: Clinical Managementmentioning
confidence: 98%
“…Sectioning of the specimen at multiple levels is necessary for a thorough histological assessment to rule out a coexistent adenocarcinoma. In a longitudinal study by Kobara et al., 18 women with suspected LEGH who did not undergo hysterectomy had periodic surveillance using MRI and cervical smears. An increasing lesion size of >38% on MRI assessment and worsening cervical cytology was closely associated with onset of malignant transformation in cases of LEGH 18 .…”
Section: Gastric‐type Adenocarcinoma and Its Precursor Lesionsmentioning
confidence: 99%
“…LEGH by itself is considered a benign lesion, but it can coexist with atypical areas, GAIS or even adenocarcinoma. LEGH may progress to GAC in 1.5% of cases, although in many instances adenocarcinoma arises de novo or from GAIS 18 . Comparative genomic hybridisation studies have shown recurrent chromosomal imbalances, in the form of gains of chromosome 3q and loss of 1p in around 20% of LEGH, with these alterations also being present in adenoma malignum and other cervical mucinous adenocarcinomas 19 …”
Section: Gastric‐type Adenocarcinoma and Its Precursor Lesionsmentioning
confidence: 99%
See 2 more Smart Citations